Lexical Meaning and Grammatical Meaning in the Lyrics of Song "Terbuang dalam Waktu" by Barasuara - Wayan Tiadilona (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe the lexical and grammatical meanings contained in the lyrics of the song "Terbuang dalam Waktu" by Barasuara based on semantic analysis. The song lyrics were chosen as the object of research because they contain rich linguistic creativity, both basic meanings and meanings formed through grammatical processes. This study used a descriptive qualitative method with data in the form of words, phrases, and clauses in the song lyrics collected through reading and note-taking techniques. Data analysis was conducted using the Miles and Huberman interactive analysis model, including data reduction, data presentation, and conclusion drawing. The results show that the song lyrics contain various forms of lexical meanings that refer to the basic meanings of words as listed in dictionaries, such as exclamation, voice, pain, pain, hope, and wound. In addition, grammatical meanings emerged from affixation, reduplication, and phrase formation processes, such as in the words "mengenang," "menepis," "perubahan," "bersahut," "bergulat," and "terbuang." The research conclusion shows that the combination of lexical and grammatical meanings in the lyrics of "Terbuang dalam Waktu" produces a rich, expressive, and emotional meaning. The lyrics not only convey a literal message through the basic meaning of the words but also convey the dynamics of change and inner nuances through their grammatical structure. This research confirms that the analysis of meaning in song lyrics has important academic value and can be used as a reference in semantic studies and Indonesian language learning.